Supervisor-Subordinate Communication and Employee Performance: A Qualitative Case Study - Suryadi Wardiana; Serius Zebua; Adrianus Risda Lega (INJECT (Interdisciplinary Journal of Communication), 2026)
Supervisor-subordinate communication is widely recognized as an important factor in employee motivation and performance. However, many previous studies have examined communication mainly as a general organizational variable, with limited attention to the relational processes through which supervisory communication is interpreted and transformed into motivational and performance-related outcomes. This study examines supervisor-subordinate communication as a relational mechanism in a hierarchical workplace context. In this study, relational mechanism refers to recurring communicative processes through which supervisory messages are interpreted by subordinates as sources of clarity, inclusion, guidance, support, and coordination. Using a qualitative case study design at PT Modella, Indonesia, this study draws on semi-structured interviews, observation, and organizational documentation involving one leadership-level key informant and five employee informants from production, packing, administration, and sales divisions. Thematic analysis identified five relational communication processes: task clarification, dialogic participation, constructive feedback, emotional support, and cross-functional coordination. These processes shaped work motivation by strengthening role certainty, perceived appreciation, psychological safety, learning orientation, and self-confidence. They also contributed to perceived performance through clearer task execution, fewer work errors, faster problem solving, and smoother inter-divisional coordination. The study contributes to organizational communication scholarship by showing that supervisor-subordinate communication influences motivation and perceived performance not only through information transmission but also through employees’ relational interpretation of supervisory interaction. The findings should be understood within the limits of a single qualitative case study and perceived rather than objectively measured performance.